At the nexus of work and family: Family farms in upstate New York. (January 2017) - Dreby, Joanna; Jung, Gowoon; Sullivan, Rachel
Abstract: Today's farm families contend with the paradox of an increase in the cultural values associated with farming and a decrease in the viability of farming as a way of life. How do families understand and organize their labor as farmers under such conditions? This paper explores the meaning of work and family for contemporary farmers in upstate New York. Drawing first on an analysis of 116 websites, we show that farm families employ four different "work-family narratives" in public representations of their farm: (a) lifestyle, (b) small business, (c) community oriented and (d) market oriented. We then turn to in-depth interviews with 39 farm families and find that families draw on these four "work-family narratives" in private explanations of their decisions to farm and gendered divisions of labor. We also find that narratives may evolve over time to adapt to changes in the household and farm business. This suggests both agency and diversity in farm families' adaptations to modern marketplace conditions. Highlights: Farm families face a paradox of an increase in values attributed to family-based farming and a decrease in its viability. Farm families employ four "work-family narratives" in response to market conditions. "Work-family narratives" involve different accounts about motivations for farming and gendered divisions of labor. "Work-family narratives" may evolve over time to adapt to changes in the household and farm business.